Interatomic Coulombic electron capture from first principles - Sisourat, Nicolas; Miteva, Tsveta; Gorfinkiel, Jimena D.; Gokhberg, Kirill; Cederbaum, Lorenz S. (Physical review, 2018)
Interatomic Coulombic electron capture (ICEC) is an environment-assisted process in which a free electron can efficiently attach to an ion, atom or molecule by transferring the excess energy to a neighboring species. Absolute cross sections are necessary to evaluate the relative importance of this process. In this work, we employ the R-matrix method to compute ab initio these cross sections for a singly charged neon ion embedded in small helium clusters. Our results show that the ICEC cross sections are several orders of magnitude higher than anticipated and dominate other competing processes. Electron energy loss spectra on an absolute scale are provided for the Ne+He20 cluster. Such spectra exhibit an unambiguous signature of the ICEC process. The finding is expected to stimulate experimental observations.
Gesehen am 14.10.2019